The effect of offensive tactical drills under defensive pressure on developing performance endurance, programmed cell death, and tactical behavior in young football players - Jawad, Asst.L.Ahmed Salem; Hussein, Prof.Dr.Ahmed Murtadha Abdul; Jawad, Prof.Dr.Alaa Faleh; Ali, Asst.L.Ihsan Abdul Latif (Sulaimani Journal for Humanities, 2026)
Modern sports training focuses on developing energy production systems and the associated functional changes. Since football also relies on the anaerobic lactic system due to its varied and high speed and the strength required in physical and tactical performance, it has become essential for coaches to utilize and concentrate on tactical training based on the lactic system and suited to the nature of the game. This includes understanding the effectiveness of these exercises in developing performance endurance and certain physiological variables, most importantly programmed cell death and offensive tactical behavior. This is where the importance of this research lies: by developing offensive tactical exercises under defensive pressure to improve players' physical and physiological levels and their tactical behavior. This contributes to developing players' performance and enables them to achieve better results in matches. The study aimed to: develop offensive tactical exercises under defensive pressure. To identify the effect of offensive tactical drills under defensive pressure on young football players. The researchers used the experimental method. The research population consisted of young players from Karbala clubs, and the research sample was randomly selected (by lottery). The sample, consisting of 20 players from Karbala Sports Club, was divided into two groups: an experimental group of 10 players and a control group of 10 players. Attacking tactical drills were used intensively (80-90%). The training sessions were conducted three times a week, on Saturdays, Mondays, and Wednesdays, over a period of 8 weeks. The most important conclusions included: a positive effect of offensive tactical drills on developing performance endurance, programmed cell death, and tactical behavior in young football players. The recommendations emphasized the necessity for coaches to use offensive tactical drills under defensive pressure and to pay attention to biochemical measurements as indicators of the adaptation of the body's functional systems and their impact on determining training status.